2020
DOI: 10.3389/fcell.2020.566530
|View full text |Cite
|
Sign up to set email alerts
|

Microglia-Derived Extracellular Vesicles Carrying miR-711 Alleviate Neurodegeneration in a Murine Alzheimer’s Disease Model by Binding to Itpkb

Abstract: Neurodegeneration in Alzheimer's disease (AD) results in microglial activation, which may participate in the inflammatory cascade accelerating tissue damage. In this study, we sought to characterize the alleviatory role of microRNA-711 (miR-711) encapsulated in microglia-derived extracellular vesicles (EVs) in a model of AD. Ultracentrifugation was employed to extract EVs from microglia (BV2 cells), which were identified using Western blot analysis of the EVs marker proteins Alix and CD63. A repetitive mild tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…LAMP1, RAB7, RAB27, CD63 and cathepsin B antibodies were then used to determine whether these proteins were altered in hippocampal lysates from zQ175 mice at 6 months of age, and the western blots of hippocampal lysates from 8- and 12-week-old R6/2 mice were repeated with a larger number of samples. We found that levels of RAB27 and CD63, both involved in MVB related exocytosis [ 24 , 54 , 82 ], were reduced in the 6-month-old zQ175 and 8- and 12-week-old R6/2 lysates (Fig. 8 ).…”
Section: Resultsmentioning
confidence: 94%
“…LAMP1, RAB7, RAB27, CD63 and cathepsin B antibodies were then used to determine whether these proteins were altered in hippocampal lysates from zQ175 mice at 6 months of age, and the western blots of hippocampal lysates from 8- and 12-week-old R6/2 mice were repeated with a larger number of samples. We found that levels of RAB27 and CD63, both involved in MVB related exocytosis [ 24 , 54 , 82 ], were reduced in the 6-month-old zQ175 and 8- and 12-week-old R6/2 lysates (Fig. 8 ).…”
Section: Resultsmentioning
confidence: 94%
“…LAMP1, RAB7, RAB27, CD63 and cathepsin B antibodies were then used to determine whether these proteins were altered in hippocampal lysates from zQ175 mice at 6 months of age, and the western blots of hippocampal lysates from 8- and 12-week-old R6/2 mice were repeated with a larger number of samples. We found that levels of RAB27 and CD63, both involved in MVB related exocytosis [53,23,80], were reduced in the 6-month-old zQ175 and 8- and 12-week-old R6/2 lysates (Fig. 8).…”
Section: Resultsmentioning
confidence: 94%
“…The role of miRNAs in microglial exosomes on regulating neurodegeneration was also demonstrated in repetitive mild TBI, important risk factor for long-term neurodegenerative disorders, such as AD. In vivo, hyperphosphorylation of Tau was reduced via injection of EVs with overexpressed miRNA-711 secreted by BV-2 human microglia cells [ 66 ]. This has been suggested to affect the neuro-immunological interactions between macrophages and sensory neurons [ 67 ].…”
Section: Neuron–microglia Crosstalk In Cns Physiology and Pathologmentioning
confidence: 99%